Patch Testing Ingredients of Dermabond and Other Cyanoacrylate-Containing Adhesives. Issue 5 (September 2019) - Cook, Kevin A.; White, Andrew A.; Shaw, Daniel W.
Abstract : Background: Cyanoacrylates are strong adhesives used for a variety of medical, industrial, and cosmetic applications and have been implicated as a cause of allergic contact dermatitis. Objective: The aim of the study was to review our experience in patch testing with cyanoacrylates. Methods: We reviewed patch test results of 38 patients with a clinical history of contact dermatitis due to a cyanoacrylate-containing adhesive (mostly Dermabond). Testing used cyanoacrylates of >99% purity diluted to 10% to 30% in petrolatum (pet.), undiluted octyl cyanoacrylate, and/or Dermabond Mini or Advanced "as is." Patch tests were also performed with methacrylates, formaldehyde (a cyanoacrylate impurity), benzalkonium chloride, and cyanoacrylate polymerization inhibitors. Three patients were also tested with Dermabond Mini on abraded skin. Results: Commercial cyanoacrylate patch testing material (ethyl cyanoacrylate 10% pet.) detected 29% of Dermabond-allergic patients, whereas patch testing with octyl cyanoacrylate 10% pet. increased detection to 50%. Testing with higher concentrations and/or on abraded skin further increased yield. Thirteen (37%) of our 35 cyanoacrylate-allergic patients were also allergic to methacrylates or acrylates. Conclusions: Octyl cyanoacrylate is the usual allergenic ingredient in Dermabond. Patch testing with high concentrations is often required. Testing Dermabond on abraded skin further improves diagnostic sensitivity by more closely simulating clinical use.